Literature Review on The Integration of Engklek Games in Physics Learning - Ajeng Wahyu Setiani; Wirawan Fadly; Utama Alan Deta (Jurnal Ilmiah Pendidikan Fisika, 2026)
The traditional game of Engklek is a hopping game played on one foot across a flat surface. Integrating local wisdom through innovative learning approaches can increase student motivation while preserving traditional culture. This study explores how the Engklek game can be implemented as an instructional medium in physics education. Using a Systematic Literature Review (SLR) with the PRISMA method, this research analyzes 10 relevant article studies published between 2021 to 2025 retrieved from the Google Scholar database and limited to those indexed in Scopus or SINTA. The analysis shows that the Engklek game explores physics concepts such as parabolic motion, Newton’s laws, energy work, momentum and impulse, torque, and rigid body equilibrium. The game proves to be an effective and enjoyable medium for physics learning. The implications of using Engklek support the development of ethophysics by connecting scientific concepts with local wisdom.